Neuropathology and underlying mechanisms of cerebral amyloid angiopathy - van Veluw, Susanne J. (Henry Stewart Talks, 2023)
Cerebral amyloid angiopathy (CAA), Cortical microinfarcts (CMI), Enlarged perivascular spaces (EPVS), Cerebral microbleeds (CMB), Cortical superficial siderosis (cSS), Vascular remodeling